The deteriorating stroke - Hacke, Werner (Henry Stewart Talks, 2008)
Causes of stroke, Pathophysiology of ischemic brain edema, Space occupying infarction, Treatment of ischemic brain edema, Causes of early deterioration after ischemic stroke, Large, space occupying edema, Edema formation after ischemic stroke, Treatment of brain edema, Pathophysiology of space occupying infarction, Delay between edema formation and ICP-elevation, Malignant MCA infarction, Clinical course, Natural history and early diagnosis, Malignant MCA and brain edema, Conservative treatment options, ICU care for ischemic stroke, Baseline therapy in severe stroke, ICP therapy in stroke, Medical therapy, Hypothermia, Decompressive surgery, The controversy: survival vs. quality of life, The reality of randomized trials for rare conditions, The 5 RCTs, Pooled analysis design, Results, Timing, The need for more evidence for the general approach and not the details
Archived at 2016/06/22